The influence of elliptical chainrings on 10 km cycling time trial performance - Peiffer, J. J.; Abbiss, C. R. (International Journal of Sports Physiology and Performance, 2010)
The use of elliptical chainrings (also called chainwheels or sprockets) has gained considerable interest in the amateur and professional cycling community. Nevertheless, we are unaware of any scientific studies that have examined the performance benefits of using elliptical chainrings during an actual performance trial. Therefore, this study examined the influence of elliptical chainring use on physiological and performance parameters during a 10 km cycling time trial. Nine male cyclists completed, in a counterbalanced order, three 10 km cycling time trials using either a standard chainring or an elliptical chainring at two distinct settings. An attempt was made to blind the cyclists to the type of chainring used until the completion of the study. During the 10 km time trial, power output and heart rate were recorded at a frequency of 1 Hz and RPE was measured at 3, 6, and 8.5 km. Total power output was not different (P = .40) between the circular (340 ± 30 W) or either elliptical chainring condition (342 ± 29 W and 341 ± 31 W). Similarly, no differences (P = .73) in 2 km mean power output were observed between conditions. Further, no differences in RPE were observed between conditions measured at 3, 6, and 8.5 km. Heart rate was significantly greater (P = .02) using the less aggressive elliptical setting (174 ± 10 bpm) compared with the circular setting (171 ± 9 bpm). Elliptical chainrings do not appear to provide a performance benefit over traditional circular chainrings during a mid-distance time trial.